Pengaruh Kualitas Pelayanan, Kelengkapan Produk Dan Harga Produk Terhadap Kepuasan Konsumen Pada “Mitra Swalayan” Kartasura - Tiara Kartika Sari; Khabib Alia Akhmad; Esti Dwi Rahmawati (Universitas 45 Surabaya, 2024)
The increasing growth of the industry now can cause competition in companies, one of which is the retail business. Where must be able to compete competitively to understand consumers. Companies need to implement more rigorous and innovative strategies in developing businesses, so as to meet the satisfaction of consumers. This study aims to determine the effect of service quality, product completeness, and product prices on customer satisfaction at